Plant responses to fungal volatiles involve global posttranslational thiol redox proteome changes that affect photosynthesis. (10th July 2019) - Ameztoy, Kinia; Baslam, Marouane; Sánchez‐López, Ángela María; Muñoz, Francisco José; Bahaji, Abdellatif; Almagro, Goizeder; García‐Gómez, Pablo; Baroja‐Fernández, Edurne; De Diego, Nuria; Humplík, Jan F.; Ugena, Lydia; Spíchal, Lukáš; et al.
Abstract: Microorganisms produce volatile compounds (VCs) that promote plant growth and photosynthesis through complex mechanisms involving cytokinin (CK) and abscisic acid (ABA). We hypothesized that plants' responses to microbial VCs involve posttranslational modifications of the thiol redox proteome through action of plastidial NADPH‐dependent thioredoxin reductase C (NTRC), which regulates chloroplast redox status via its functional relationship with 2‐Cys peroxiredoxins. To test this hypothesis, we analysed developmental, metabolic, hormonal, genetic, and redox proteomic responses of wild‐type (WT) plants and a NTRC knockout mutant ( ntrc ) to VCs emitted by the phytopathogen Alternaria alternata . Fungal VC‐promoted growth, changes in root architecture, shifts in expression of VC‐responsive CK‐ and ABA‐regulated genes, and increases in photosynthetic capacity were substantially weaker in ntrc plants than in WT plants. As in WT plants, fungal VCs strongly promoted growth, chlorophyll accumulation, and photosynthesis in ntrc – Δ2cp plants with reduced 2‐Cys peroxiredoxin expression. OxiTRAQ‐based quantitative and site‐specific redox proteomic analyses revealed that VCs promote global reduction of the thiol redox proteome (especially of photosynthesis‐related proteins) of WT leaves but its oxidation in ntrc leaves. Our findings show that NTRC is an important mediator of plant responses to microbial VCs through mechanisms involving global thiol redox proteome changes that affect photosynthesis. Abstract : Fungal volatile compounds (VCs) promote growth, photosynthesis, root architecture changes, and shifts in expression of VC‐responsive cytokinin‐ and ABA‐regulated genes in WT plants. These changes were substantially weaker in ntrc plants. The weak response to fungal VCs of ntrc plants was suppressed by decreased 2‐Cys peroxiredoxin expression. Fungal VCs promote global reduction of the thiol redox proteome (especially of photosynthesis‐related proteins) of WT leaves but its oxidation in ntrc leaves. Our findings show that NTRC mediates the response to microbial VCs through mechanisms involving hormone signalling and global thiol redox proteome changes that affect photosynthesis.